Data on the impact of rain events on FCH4 from hemiboreal, boreal, and subarctic lakes - Sieczko, Anna Katarzyna (Linköping University, 2023)
The main objective of the study resulting in these data, was to assess the short-term impact of typically occurring rain events with different intensity on FCH4 from various lake types located in hemiboreal, boreal, and subarctic Sweden. Two lakes: Ljusvattentjärn (LJE) and Parsen (PRS) are surrounded by coniferous forest whereas Erssjön (ERS) and Venasjön (VEN) are located in mixed agricultural and forest catchments. The lake BD4 is situated in mainly treeless subarctic tundra with a sparse presence of mountain birch. The average recorded yearly precipitation (1991–2020) in the catchment of each lake is 610 mm (VEN), 610 mm (PRS), 590 mm (LJE), 900 mm (ERS) and 860 mm (BD4).

FCH4 measurements associated with rain events covered different periods in the different lakes. LJE and ERS were investigated in the summer (July 11–August 22) and fall (September 12–November 30) of 2017, respectively. The remaining lakes were sampled in the fall and summer of 2018: VEN (June 15–September 25), BD4 (July 04–July 27) and PRS (September 27–October 27).

To investigate if rain could impact FCH4 measured at different lake locations with varying depths, the lakes were divided into three zones. Zone 1 covered the lake area directly adjacent to the shore, with depths ranging 0–1 m. Due to the very steep shoreline in several lake locations, we also included FCH4 measured at slightly deeper areas (up to 1.5 m) but very close to the shore in zone 1. Zone 2 covered lake area with depths between 1 m (1.5 m) to 3 m, whereas zone 3 included FCH4 measured at 3 to 8 m depths. Depending on the lake, we measured FCH4 with either manual or automated flux chambers (AFCs).

To assess temporal variability of FCH4 in relation to precipitation events, averages of FCH4 before, during, and after the events were calculated. These averages were calculated for each lake and chamber, over periods of 2 h for VEN, PRS and LJE and over periods of 8 h or 12 h in ERS and BD4 due to lower resolution of FCH4 measured in these two lakes.

See "Minor impacts of rain on methane flux from hemiboreal, boreal, and subarctic lakes" by Sieczko et al (2023) for further details.

The dataset was originally published in DiVA and moved to SND in 2024.

Syftet med studien som resulterade i dessa data var att bedöma den kortsiktiga effekten av typiskt förekommande nederbörd med olika intensitet på FCH4 från olika sjötyper belägna i hemiboreala, boreala och subarktiska Sverige. De fyra sjöar som undersökts är Ljusvattentjärn (LJE), Parsen (PRS), Erssjön (ERS) och Venasjön (VEN).

Se engelsk version av denna katalogpost, samt artikeln "Minor impacts of rain on methane flux from hemiboreal, boreal, and subarctic lakes" av Sieczko et al (2023) för ytterligare beskrivning av data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on the impact of rain events on FCH4 from hemiboreal, boreal, and subarctic lakes
Data set associated with the manuscript Minor impacts of rain on methane flux from hemiboreal, boreal, and subarctic lakes by Sieczko et.al 2023
Keywords: rainwater; regnvatten; lakes; sjöar; rain; regn; rainfall; nederbörd; methane; metan; Natural Sciences; Naturvetenskap